Formal Business Strategy and Its Impact on SME Performance: A Mediation Analysis by Competitive Advantage - Acep Fatchuroji; Candra Agus Wahyudhi; Samuel Waas (Nusantara Journal of Multidisciplinary Science, 2024)
This study aims to explore the impact of formal business strategy planning on the performance of Micro, Small, and Medium Enterprises (MSMEs), considering the mediating role of competitive advantage strategies. In the context of increasingly fierce business competition, MSMEs need to engage in systematic business strategy planning to remain competitive and grow. This research employs a quantitative method by collecting data from 139 owners and managers of textile and miscellaneous MSMEs in Merauke Regency. Data analysis in this study is conducted using Structural Equation Modeling (SEM) to evaluate the relationships among formal business strategy planning, competitive advantage strategies, and the performance of Micro, Small, and Medium Enterprises (MSMEs). The results indicate that formal business strategy planning has a significant and positive effect on the performance of MSMEs. Additionally, competitive advantage strategies serve as a mediator in the relationship between formal business strategy planning and MSME performance. These findings suggest that MSMEs implementing formal business strategy planning can enhance their overall performance, particularly when accompanied by effective competitive advantage strategies. This study makes a significant contribution to the literature on business strategy and offers practical recommendations for MSME owners and managers to improve business performance through structured planning and a focus on competitive advantage.